Microplastic pollution in freshwater sediments: abundance and distribution in Selangor River Basin, Malaysia - Mohd Zaki, Muhammad Rozaimi; Sukatis, Fahren Fazzer; Jori Roslan, Muhammad Qusyairi; Mohd Isa, Noorain; Md Yusoff, Fatimah; Aris, Ahmad Zaharin (Springer Dordrecht, 2023)
Microplastic pollution has received growing interest due to its persistence and detrimental effects on humans and aquatic organisms. While microplastics in marine sediment have received a lot of attention, microplastics in riverine sediment, particularly in river basins, remain scarce. Therefore, sediment sample was collected from 25 sampling points along the Selangor River Basin and its urbanized tributaries. Microplastics were observed and identified using stereomicroscope and Fourier transform infrared spectroscopy with attenuated total reflection (FTIR-ATR). The results indicated that microplastics were present in all sediment samples, with concentrations ranging from 10 to 55 particles/kg. Small microplastics (< 300 μm) dominated more than half of all microplastics observed, with black color and bead-shaped being the most common characteristic. Polypropylene, polyester, and polyethylene were the primary polymer compositions of the microplastics. The findings suggest that anthropogenic activities from residential, agricultural, and industrial sources may contribute to the ubiquity of microplastics in river. These results highlight the need for further monitoring assessment and proactive measures to mitigate microplastic pollution in riverine environments.